2013 IEEE/RSJ International Conference on Intelligent Robots and Systems 2013
DOI: 10.1109/iros.2013.6697101
|View full text |Cite
|
Sign up to set email alerts
|

Augmenting traversability maps with ultra-wideband radar to enhance obstacle detection in vegetated environments

Abstract: Operating in vegetated environments is a major challenge for autonomous robots. Obstacle detection based only on geometric features causes the robot to consider foliage, for example, small grass tussocks that could be easily driven through, as obstacles. Classifying vegetation does not solve this problem since there might be an obstacle hidden behind the vegetation. In addition, dense vegetation typically needs to be considered as an obstacle. This paper addresses this problem by augmenting probabilistic trave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Unfortunately, it is not always enough for safe navigation to be able to distinguish vegetation from other obstacles, because there might be an obstacle hidden behind the vegetation. This problem was addressed in a recent study, in which UWB radar was used in parallel with LIDAR to augment traversability maps in vegetated environments (Ahtiainen et al., , ). It was shown that because the utilized UWB radars are capable of penetrating around 40cm of vegetation, it is possible to generate accurate traversability maps of densely vegetated environments such that solid obstacles hidden behind dense vegetation can still be detected.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, it is not always enough for safe navigation to be able to distinguish vegetation from other obstacles, because there might be an obstacle hidden behind the vegetation. This problem was addressed in a recent study, in which UWB radar was used in parallel with LIDAR to augment traversability maps in vegetated environments (Ahtiainen et al., , ). It was shown that because the utilized UWB radars are capable of penetrating around 40cm of vegetation, it is possible to generate accurate traversability maps of densely vegetated environments such that solid obstacles hidden behind dense vegetation can still be detected.…”
Section: Related Workmentioning
confidence: 99%
“…This constraint may be relaxed in future works by fusing our traversability results with classifications based on the algorithms proposed in Ahtiainen et al. () and Ahtiainen et al. ().…”
Section: Related Workmentioning
confidence: 99%
“…A recent and very complete survey on the terrain traversability analysis for autonomous ground vehicles is presented in [212]. The authors define a taxonomy for the different methods by grouping them into vision-based (e.g., [213,214]), LiDAR-based (e.g., [215,216]), alternative sensor-based (e.g., [217][218][219]), and sensor fusion methods (e.g., [220,221]).…”
Section: Traversability Analysis For Navigationmentioning
confidence: 99%